Developing Sustainable Agromining Systems in Agricultural Ultramafic Soils for Nickel Recovery - Kidd, Petra Susan; Bani, Aida; Benizri, Emile; Gonnelli, Cristina; Hazotte, Claire; Kisser, Johannes; Konstantinou, Maria; Kuppens, Tom; Kyrkas, Dimitris; Laubie, Baptiste; Malina, Robert; Morel, Jean-Louis; et al. (Frontiers in Environmental Science, 2018)
Ultramafic soils are typically enriched in nickel (Ni), chromium (Cr), and cobalt (Co) and deficient in essential nutrients, making them unattractive for traditional agriculture. Implementing agromining systems in ultramafic agricultural soils represent an ecological option for the sustainable management and re-valorisation of these low-productivity landscapes. These novel agroecosystems cultivate Ni-hyperaccumulating plants which are able to bioaccumulate this metal in their aerial plant parts; harvested biomass can be incinerated to produce Ni-enriched ash or “bio-ore” from which Ni metal, Ni ecocatalysts or pure Ni salts can be recovered. Nickel hyperaccumulation has been documented in ~450 species, and in temperate latitudes these mainly belong to the family Brassicaceae and particularly to the genus Odontarrhena (syn. Alyssum pro parte). Agromining allows for sustainable metal recovery without causing the environmental impacts associated with conventional mining activities, and at the same time, can improve soil fertility and quality and provide essential ecosystem services. Parallel reductions in Ni phytotoxicity over time would also permit cultivation of conventional agricultural crops. Field studies in Europe have been restricted to Mediterranean areas and these only evaluated the Ni-hyperaccumulator Odontarrhena muralis s.l. Two recent EU projects (Agronickel and LIFE-Agromine) have established a network of agromining field sites in ultramafic regions with different edapho-climatic characteristics across Albania, Austria, Greece and Spain. Soil and crop management practices are being developed so as to optimize the Ni agromining process; field studies are evaluating the potential benefits of fertilization regimes, crop selection and cropping patterns, and bioaugmentation with plant-associated microorganisms. Hydrometallurgical processes are being up-scaled to produce nickel compounds and energy from hyperaccumulator biomass. Exploratory techno-economic assessment of Ni metal recovery by pyrometallurgical conversion of O. muralis s.l. shows promising results under the condition that heat released during incineration can be valorized in the vicinity of the processing facility.